2013
DOI: 10.1159/000346225
|View full text |Cite
|
Sign up to set email alerts
|

A Worldwide Survey of the Current Daily Practice in Liver Surgery

Abstract: Background: Liver resection remains the mainstay of curative treatment for liver malignancies. A variety of preoperative assessments and surgical techniques have improved the short- and long-term outcomes of liver resection in patients with liver tumors. Recently, laparoscopic hepatectomies have been increasingly performed. The aim of the present study is to survey the current practice of liver surgery in high-volume centers in the world. Methods: A questionnaire on the preoperative assessment for liver surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 72 publications
2
70
0
Order By: Relevance
“…Both groups of donors did not receive any blood transfusion peri-operatively. No significant between-group difference was observed in median (IQR [range]) hospital stay after operation: 11 (10-13 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]) days in the control vs 11 (10-13 [10][11][12][13][14][15][16][17][18][19][20]) days in the high SVV group, p = 0.621.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups of donors did not receive any blood transfusion peri-operatively. No significant between-group difference was observed in median (IQR [range]) hospital stay after operation: 11 (10-13 [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]) days in the control vs 11 (10-13 [10][11][12][13][14][15][16][17][18][19][20]) days in the high SVV group, p = 0.621.…”
Section: Resultsmentioning
confidence: 99%
“…Although maintaining a low CVP SVV, stroke volume variation; INR, international normalised ratio; AST, aspartate aminotransferase; ALT, alanine aminotransferase; cGT, gamma-glutamyl transpeptidase. (≤ 5 mmHg) is frequently used to minimise blood loss during hepatectomy, this is considered controversial, especially in living liver donors [1,10,11,21,22]. For example, CVP was reported not to correlate with pre-load status in normal healthy volunteers [23], and several studies in living liver donors showed that CVP during hepatic resection was not associated with intraoperative blood loss [5,8,9,22].…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) has been accepted as an equivalent alternative to resection as an eradicative treatment for small HCC [2]. However, the local tumor progression (LTP) rate after RFA is higher than that after surgical resection [3,4]. Several studies have indicated that the incidence of LTP after RFA ranges from 2% to 18% [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The total number of cases encountered was 63. Treatment was resection [1] in 40 cases, transcatheter arterial chemoembolization []2] in 2 cases, and careful follow-up in 21 cases. The ways in which diagnosis came about were as follows: tumor rupture (n = 4), incidental detection on screening (n = 25), referral from another hospital or clinic (n = 32), and other (n = 2).…”
Section: Nationwide Survey In Japanmentioning
confidence: 99%